Unearthing how Jamaican secondary students have made sense of the traditional meanings of academic performance and academic success - Keshinro, Khummit; Tissot, Cathy; Foley, Catherine (Taylor and Francis, 2024)
The Caribbean Examinations Council data from 2011 to 2021 for the Caribbean Secondary Examination Certificate (CSEC) Council (2011–2021) shows many Jamaican secondary students failing to pass the Mathematics and English examinations. Discussions on the failings have focused on adults’ views, excluding student’s voices. This study sampled twelve 15–16-year-old rural Jamaican secondary students to hear their understanding and interpretation of academic performance and success and how these terms should be defined. A convenience sample and an interpretivist paradigm within a social constructionism framework were applied. Data was collected using photovoice, audio journaling, one-on-one interviews, and focus group discussion; a focus coding technique was used to find themes and present the findings. The data showed participants understood the definitions of the terms but interpreted them as stereotyping labels that adversely impacted many students’ performance and post-secondary success. The findings underscore the importance of hearing students’ voices to better understand academic outcomes.
Keywords: academic performance; academic success; benchmarks; stereotyping labels; secondary students